다문화시대 북한이탈주민정책의 개선 방향 - 김창근; Kim Chang-geun (윤리연구, 1(109), 2016)
다문화시대의 사회적응은 이주사회와 이주민이 쌍방향에서 사회문화적으로 적응해가는 과정이며, 사회통합은 다양성 속의 통합성을 이루어 동등한 시민적 정체성을 갖게된 상태이다. 그간의 이탈주민정책은 초기의 생활보호 및 정착지원에 초점을 두면 이탈주민이 민족동질성에 기초해 우리 사회에 잘 정착하리라는 기대를 깔고 있었다. 민간보다는 정부에 대한 의존이 컸고, 통합보다는 적응에 대한 관심이 많았으며, 시민정체성 보다는 민족정체성에 기반했다. 하지만, 이탈주민은 남한 주민과 대등한 시민적 위치에서 상호관계하면서, 상호 변화되어가는 과정을 사회적응이자 사회통합으로 보았다. 다문화시대 이탈주민정책은 일방주의적 기대 혹은 동화주의적 접근에 관한 부분을 개선하고 쌍방향적인 통합주의적 접근이 이루어지도록 해야 한다. 일상에서부터의 다문화주의적 접근을 통해 남한 주민과 이탈주민간의 상호관계성이 증대되도록 해야 한다. 혈연 혹은 민족 중심적인 인종적 정체성에 기반한 정책은 재고하고 이탈주민을 동료시민으로 보는 시민적 정체성에 근거한 정책이 구체화되어야 한다. 이탈주민의 자립·자활 능력을 배양하기 위한 정부-지자체-민간간의 유기적 연계와 다각도의 정책이 지속적으로 추진되어야 한다. 이탈주민이 갖는 정치성이나 상징성, 우리 사회의 동포애적 기대, 통일의 경제적 편익 등의 관점에서 이탈주민정책의 당위성을 찾던 시각은 개선되어야 한다. 사회적 정의, 인도주의, 보편가치, 시민행위자, 동반자 등과 같은 규범적 준거에 기반하여 이탈주민정책에 대한 사회적 지지와 합의를 확대해가도록 노력해야 한다. Social adaptation in multicultural age is the sociocultural adapting process of interaction between migrant community and immigrants, and the social integration is the states which has equivalent civil identities by forming unity within diversity. We have expected that policy for North Korean defectors would help them seccessfully to adapt the our society based on national homogeneity if the policy was focused on the intial livelihood protention and support for settlement. We have relied on the government rather than civilian, paid attention to the adpation rather than intergrity, and focused on national identity rather than civic identity. However, having interrelation between South Korean and North Korean defectors on equivalent civic position for harmonization, North Korean defectors have regarded changing process of each other as social adaption and social integration. The policy for North Korean defectors in multicultural age should be reformed the parts of one-sided expectation and assimilational approach, and should be improved interactive integrational approach. Through the multicultural approach in daily life, interrelation between South Korean and North Korean defectors should be increased. The policy based on ethnic identity which centered blood ties and race should be reconsidered, instead the policy based on civic identity which treating North Korean defectors as fellow citizens should be actualized. The organic connection of government-local government-private organization and the various policy for cultivating self-reliance and self-support ability of North Korean defectors should steadily be pushed ahead. We should reform the perspective to find out appropriateness from the view of political nature and symbolizm of North Korean defectors, fraternal expectation of our society, and economic benefit of unification should be reformed. Based on normative standard, such as social justice, humanitarianism, value of universality, citizen performer, and companion, we have to try to expand social support and agreement of the policy for North Korean defectors.